Neural and hormonal mechanisms of appetite regulation during eating - Sun, Xurui; Liu, Binghan; Yuan, Yuan; Rong, Ying; Pang, Rui; Li, Qiu (Frontiers in Nutrition, 2025)
Numerous animal and clinical studies have demonstrated that the arcuate nucleus of the hypothalamus, a central regulator of appetite, plays a significant role in modulating feeding behavior. However, current research primarily focuses on long-term dietary changes and their effects on the body, with limited investigation into neuroendocrine dynamics during individual meals across diverse populations. In contrast to long-term dietary adjustments, directives for dietary behavior during a specific meal are more actionable, potentially enhancing patient adherence and achieving better outcomes in dietary behavior interventions. This review aimed to explore the neural pathways and endocrine changes activated by gastrointestinal expansion and variations in blood nutrient levels during a single meal, with the goal of informing dietary behavior guidance.